Determinants of Corporate Internet Financial Reporting in Asia-Pacific Countries: A Cross Country Analysis - Cut Nadhirah Faisal; Yossi Diantimala; Dinaroe Dinaroe (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
The purpose of this study is to provide a comparative analysis of the quality of Corporate Internet Financial Reporting (CIFR) practices in the Asia Pacific. It examines the impact of firm size, listing age, internationalization, and auditor size on CIFR practices. The population in this study are all publicly listed companies in Australia, Singapore, and Indonesia. The sample comprises of non-financial companies in 2019, namely 95 Australian companies, 87 Singapore companies, and 85 Indonesian companies. Multivariate analysis is used to examine the hypothesis. The results show that Singapore and Indonesian firms have higher CIFR disclosure compared to Australia. This study found that some firm characteristics explain the level of CIFR disclosure. Firm size, internationalization, and auditor type have a significantly positive impact to CIFR disclosure in the Asia Pacific, while listing age does not explain the level of the CIFR.